WaveT, a custom device able to measure viscoelastic properties of wood under water-saturated conditions - Placet, Vincent; Passard, Joëlle; Perré, Patrick (Maderas. Ciencia y Tecnología, 2014)
This work presents an original experimental device conceived to characterise the viscoelastic properties of wood. Classically, the dynamic mechanical analysis of wood is performed using a commercial apparatus like a DMA (Dynamic Mechanical Analyser). However, when analysing wood with this type of apparatus, many problems related to the hygroscopic behaviour and the orthotropic structure of wood may be encountered. This is why an original apparatus perfectly adapted to the wood features has been developed. The WAVET is able to measure the viscoelastic properties of wood samples under water-saturated conditions, in the temperature range of 5°C to 95°C at frequencies varying between 0.005 Hz and 10 Hz. Samples are tested in a cantilever configuration. The whole experiment has been designed to withstand the severe conditions of temperature and humidity. At the same time, an analytical model based on Kelvin’s elements has been developed. This model is able to correct experimental measurements performed close to the resonance frequency. Results obtained for beech samples in radial and tangential directions using the WAVET and a commercial apparatus (DMA 2980 TA Instruments) are compared and discussed. This comparison underlines the relevance of the WAVET device.